The role of a pluralistic extension system in enhancing agriculture productivity in Mozambique - Gemo, Helder R.; Stevens, J.B.; Chilonda, Pius (2013)
This paper presents an overview of the characteristics and roles of key role-players involved in agricultural development in Mozambique. As in many other countries worldwide, extension service provision is characterised by the multiple service providers responding to the needs and demands of farmers. This is unlike in the recent past when agricultural services were mainly delivered by the public sector. The 25 years of public extension have been characterised by different degrees of progress. Supporting extension policy was developed and amended as required during this period, which impacted positively on farmer coverage (number of districts operating) as well as the number of farmers served per extensionist. The expansion of public extension services created new challenges for the delivering of extension services. Within the pluralistic extension system of Mozambique, NGO's and private commodity extension organisations play an important role in supporting smallholder farmers. To be able to learn from the different experiences in offering extension by the various service providers is only possible through effective communication and sharing of experiences between public, NGO's and private extension service providers. Despite some local based initiatives seeking to enhance collaboration between public and NGOs extension, no official extension platform (multi stakeholder) at national level exists which can take care of the coordination and management of the pluralistic extension system.